HKCV Rheological Constitutive Model of Mudstone under Dry and Saturated Conditions - Xingang Wang; Lei Huang; Changbin Yan; Baoqin Lian (Advances in Civil Engineering)
Triaxial rheological tests are performed on mudstones collected from the soft interlayer in the Three Gorges Reservoir Area. In the tests, both dry and saturated conditions are considered, and a complete rheological process is then observed. Based on such laboratory observations of stress-strain, a four-element rheological constitutive model is developed, which is composed of (i) the Hook element, (ii) the Kelvin element, (iii) the viscoelastic-plastic body, and (iv) the nonlinear viscous body (HKCV model). The HKCV model adopts the one-dimensional and three-dimensional equations that are derived. The rheological parameters required are identified, allowing the successful development of the HKCV model. A comparison with the laboratory test observations and the existing model estimates shows that the estimates of the HKCV model are relatively consistent with the observations of the triaxial rheological test. The HKCV model better characterizes the rheological process than the three existing models. However, the HKCV model has the limitation of requiring more parameters than the existing models.